2018
DOI: 10.1038/s41534-018-0094-y
|View full text |Cite
|
Sign up to set email alerts
|

Endurance of quantum coherence due to particle indistinguishability in noisy quantum networks

Abstract: Quantum coherence, the physical property underlying fundamental phenomena such as multi-particle interference and entanglement, has emerged as a valuable resource upon which modern technologies are founded. In general, the most prominent adversary of quantum coherence is noise arising from the interaction of the associated dynamical system with its environment. Under certain conditions, however, the existence of noise may drive quantum and classical systems to endure intriguing nontrivial effects. In this vein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…Recently, it has been shown that coherences arising from particle indistinguishability are robust against noise [24,38]. By making use of our model, we have verified that in the steady-state, coherences accounting for particle indistinguishability do survive the impact of stochastic fluctuations in the coupling between sites (see appendix C for details).…”
Section: Two-particle Wavefunction Dynamicssupporting
confidence: 62%
See 4 more Smart Citations
“…Recently, it has been shown that coherences arising from particle indistinguishability are robust against noise [24,38]. By making use of our model, we have verified that in the steady-state, coherences accounting for particle indistinguishability do survive the impact of stochastic fluctuations in the coupling between sites (see appendix C for details).…”
Section: Two-particle Wavefunction Dynamicssupporting
confidence: 62%
“…To elucidate the effect of the stochastic coupling between sites, we now compute the dynamics of a single excitation in a fully connected network composed by three sites. We have chosen this configuration, because it constitutes the simplest quantum network that one can investigate both theoretically and experimentally [5,24]. The energies of the sites are arbitrarily chosen to be ω 1 =ω 2 =ω 3 =5 ps −1 , whereas the coupling between them are set to κ 12 =1 ps −1 , and κ 13 =κ 23 =0.5 ps −1 .…”
Section: Single-particle Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations